The Role of Internet of Services (IoS) on Industry 4.0 Through the Service Oriented Architecture (SOA) - Reis, Jacqueline Zonichenn; Gonçalves, Rodrigo Franco (Advances in Production Management Systems. Smart Manufacturing for Industry 4. 0, 2018)
Many different concepts and approaches have been seen for an Industry 4.0 achievement. In the attempt of merging the theory to the practice, there are gaps to determine which concept or technology suits best the productive chain and what is really a pre-requisite to classify it as Industry 4.0. On scientific and empirical literature about this subject, the Internet of Services, IoS, has been mentioned as an important pillar for Industry 4.0, coupled with Internet of Things (IoT) and Cyber-physical systems (CPS). While IoT and CPS as well as their link with Industry 4.0 are detailed in many researches, a deeper understanding on the Internet of Services and its contribution for this scenario is still missing. This paper aims to fill this gap gathering concepts about the Internet of Services, how it is composed and what would be its role on the manufacturing environment. Through a deeper understanding about the origin of the term Internet of Services, there is an important concept that may explain how the Industry 4.0 operates in a business and technological perspective: the concept of SOA - Service Oriented Architecture.